SALURAN PEMASARAN KAYU PERTUKANGAN JENIS BAMBANG LANANG (Michelia champaca) YANG MENGUNTUNGKAN PETANI DI SUMATERA SELATAN - Sri Lestari; Bondan Winarno; Bambang Tejo Premono (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
This research aim to marketing actors, pattern of marketing channels and marketing efficiency of bambang lanang woods study in Lahat and Empat Lawang Regencies, Data collection was conducted through interview with respondents. The respondents were purposively selected. The data was analyzed qualitatively and quantitatively. The results of research showed that the actors of research showed involved in marketing of bambang lanang wood are farmers, chainsaw men, traders, timber depot sill/furniture industries and end consumers. In the study of areas, marketing channels of bambang lanang wood are found. Among the five patterns of the marketing channel, the quite high farmer's share (40.91%) occured at marketing channel pattern 1 (farmers – chainsaw men – traders – timber depot – sill/furniture industries and end consumers), pattern 2 (farmers – chainsaw men – timber depot – sill/furniture industries and end consumers) and pattern 3 (farmers – traders – timber depot –sill/furniture industries and end consumer). The most efficient marketing channel is pattern 2. The farmers need to be given information on efficient marketing channel which is favourable for them.